2022
DOI: 10.1109/tns.2022.3169756
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark Between Measured and Simulated Radiation Level Data at the Mixed-Field CHARM Facility at CERN

Abstract: A benchmark between various radiation monitors employed at CERN for radiation to electronics applications and their simulated values with the FLUKA Monte Carlo is performed at the CHARM mixed-field irradiation facility. Comparisons are made for different operational conditions, using data recorded in the 2015-2018 period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The operation of particle accelerators at CERN generates a mixed radiation field that contains different types of particles with broad energy ranges [19]. The composition of the radiation field varies significantly depending on the accelerator under exam, on the position within the accelerator, and on the amount of shielding between the radiation source and the location of interest.…”
Section: The Lhc Mixed Radiation Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The operation of particle accelerators at CERN generates a mixed radiation field that contains different types of particles with broad energy ranges [19]. The composition of the radiation field varies significantly depending on the accelerator under exam, on the position within the accelerator, and on the amount of shielding between the radiation source and the location of interest.…”
Section: The Lhc Mixed Radiation Fieldmentioning
confidence: 99%
“…In Section 2, the discussion begins by presenting the key features of the radiation environment in the tunnel of the Large Hadron Collider (LHC) [15], simulated using the FLUKA Monte Carlo code [16][17][18], CERN distributed, version 4.3.3. The radiation field includes different kinds of particles with broad energy spectra, all originating from the loss of TeV-scale beam particles or secondary collision products [19]. After this, a detailed description of the Timepix3 Radiation Monitor is presented in Section 3, starting from the hardware setup and the Timepix detection principle based on the measurement of the time-over-threshold (ToT) and time-of-arrival (ToA).…”
Section: Introductionmentioning
confidence: 99%
“…Schematic top view drawing of the CHARM facility with the highlighted detector testing positions: m5, m6, and G0. Adapted from: [12]. target (the most frequently Cu).…”
Section: A Charm Facilitymentioning
confidence: 99%
“…In addition to system-level irradiation tests, the CHARM facility is used as a validation for dosimeters and radiation monitors intended for the accelerator's mixed-field monitoring, for example for Distributed Optical Fibre Radiation Sensor (DOFRS) [6] or RadMONs [7], [8]. The facility provides multiple instruments for radiation monitoring, together with the validated simulations in the FLUKA Monte Carlo code [9]- [12]. This work extends the previous studies that demonstrated the use of a 300 µm PIPS silicon detector for heavy-ion beams characterisation [13]- [15], to a characterisation of the CHARM's mixed-field.…”
Section: Introductionmentioning
confidence: 99%
“…component level testing fluxes typically need to reach ∼10 8 p/cm 2 /s in some cases, combined SEE/cumulative damage is desirable -System level tests performed in mixed-field facilities [40], in order to account for both stochastic and cumulative damage…”
Section: Environment and Application Key See Testing Requirementsmentioning
confidence: 99%